Updated regulation on certification of citrus propagating material in the Mediterranean region - D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
An updated regulation for the certification of citrus propagating material is presented, taking into account the EPPO standards, other European certification schemes and the current phytosanitary problems of the citrus industry in the Mediterranean region. The technical protocols for the production, conservation and use of healthy propagative material are based on the recent advances in pathogen detection and elimination in Citrus spp. and on the gaps in the running certification programmes. Most of the methods and procedures included in the protocols have been validated in the framework of the MNCC activity.